D-dimer: The Risk Factor of Children's Severe Mycoplasma Pneumoniae Pneumonia - Qiu, Juan; Ge, Jin; Cao, Ling (Frontiers in Pediatrics, 2022)
Objective Mycoplasma Pneumoniae (MP) is an important cause of community-acquired pneumonia in children, which can cause serious consequences. There has been some research into predicting Severe Mycoplasma Pneumoniae Pneumonia (SMPP) primarily focused on pre-treatment time by macrolide, pre-hospital course, CRP and LDH et.al. while seldom reporting on concoagulation status. We designed this retrospective study to compare the difference between SMPP and Non-severe MPP (NSMPP) with an attempt to find the risk factors, with a special focus on concoagulation status. Method We performed a retrospective study of 786 MPP patients who were hospitalized from January 1, 2016 to December 31, 2018, age ranging from 28 days to 18 years old. All patients were divided into SMPP group and NSMPP group. A univariate analysis was conducted between both groups. The factors with statistical differences were included in logistic regression analysis to summarize the predictors of SMPP. Next, the predictive value of each risk factor was calculated from the receiver operating characteristic curve (ROC curve). Patients who had D-dimer records were divided into the elevated D-dimer group (D-dimer > 308ug/L) and the control group (D-dimer ≤ 308ug/L), and the clinical manifestations were compared. Results There was no significant difference in gender, age, pre-treatment time by macrolide, the white blood cell counts (WBC), Fibrinogen (FIB), Activated Partial Prothrombin Time (APTT), Prothrombin Time (PT) and Thrombin Time (TT) between SMPP and NSMPP. Compared with NSMPP, the pre-hospital course of SMPP was longer (P < 0.05), the neutrophil ratio (N%), platelet Count (PLT), C-reactive Protein (CRP), Lactate Dehydrogenase (LDH) and D-dimer were significantly higher (P < 0.01). The binary logistic regression analysis showed that the N%, PLT, CRP, LDH and D-dimer were the key predictors for SMPP, the N% > 67%, OR = 3.233, PLT > 445 × 109 /L, OR = 2.589, LDH > 354U/L, OR = 4.335 and D-dimer level > 403 ug/L, OR = 7.316. The D-dimer possessed the best predictive value. The incidence of complications such as pleural effusion, myocardial and liver damage of MPP was higher in the elevated D-dimer group than that in the control group (P < 0.05). Conclusion The N%, PLT, CRP, LDH and D-dimer were risk factors for SMPP. D-dimer was the best predictor among them. MPP patients with D-dimer > 308ug/L had more complications such as pleural effusion, myocardial and liver damage. More attention should be given in the treatment for this group.